Binary Oppositions in the Visual Characterizations of the English Textbook for Indonesian Junior High School Students - Gede Wisma Krisna Ari Aditya Blangsinga; Ni Komang Arie Suwastini; Made Hery Santosa; Zulidyana Dwi Rusnalasari (Universitas Pendidikan Ganesha, 2026)
Textbooks could be used to sustain or destabilize patriarchal binary oppositions, which associate women with inferior traits and roles to men. The present study aims to evaluate the visual images of the characters in an English textbook used by Indonesian ninth-grade students in junior high school, focusing on the possibility of deconstructive characterizations in these images. This study adopted interactive data analysis from Miles, Huberman, and Saldana (2014), and Millet's (2000) conception of patriarchal binary oppositions. It was revealed that the textbook's visual images assign stereotypical feminine traits and characterizations to female characters, such as grace, domesticity, passivity, caring, and fearfulness. On the other hand, the male character was portrayed as masculine, with traits such as handsome, proud, manly, active, and strong. However, some feminine traits are also attributed to male characters, while some masculine traits are assigned to female characters. Thus, despite the pervasiveness of gendered stereotypes in the visual images analyzed, a partial and constrained shift in deconstructing gender stereotypes is present.